Análise de falhas aplicada à compatibilidade de projetos na construção de edifícios - Claudia Maria Kattah Vanni (1999)
The increasing market requirements as to building quality, as well as the cost reduction pressure have demanded from building companies the adaptation of their strategies due to this emerging market conjuncture. In this context, the activities of building design must be object of managerial actions that effectively ensure an expected level of quality as a previous action to its deployment. The present work approaches the theme of compatibility of building designs in thecontext of the Total Quality Management. Initially, a critical review focusingdesign compatibility is done, showing its importance in terms of cost, quality and building time. A design compatibility method is proposed, based on the tools of failure analysis used by other industrial segments, particularly the FMEA (Failure Modes and Effects Analysis). The method allows the detection of potential failures related to the compatibility among the different building designs, its prioritization and the establishment of countermeasures against those failures, in a way to establish guidelines, which should be incorporated during the elaboration of the distinct designs. The principles involved in theelaboration of the method are based on the lean thinking school, in such a way that special attention is given to the incompatibilities caused by the information flows among distinct designs. A preliminary critical analysis of the proposed method shows that it is flexible, i.e., adaptable to the reality of different construction companies, easily implemented, and allows a gradual establishment of design optimization procedures concerned to constructability.